Proceedings, 3rd International Conference of Mechanical Engineers and 8th Annual Paper Meet on E-manufacturing, the Institution of Engineers, Bangladesh - Khondoker, M. Reaz H.; Mashiur Rahaman, Md (The Institution, 2003)
Contributed articles presented at the two conferences held on 20th-22nd March 2003 at Institution of Engineers, Bangladesh.